The Dance-In and the Re/production of White Corporeality - Kraut, Anthea (The International Journal of Screendance, 2019)
This essay examines the figure of the “dance-in,” a stand-in who dances in place of a star prior to filming, focusing on two women who acted as surrogates and dance coaches for the mid-twentieth century white film star Betty Grable: a white woman named Angie Blue and an African American woman named Marie Bryant. Bringing together film studies theories of indexicality, performance studies theories of surrogation, and critical race theories of flesh and body, I argue that the dance-in helps expose how the fiction of white corporeality as a bounded and autonomous mode of being is maintained. ERRATUM (August 27, 2020) In the article "The Dance-In and the Re/production of White Corporeality" by Anthea Kraut (The International Journal of Screendance, Vol. 10, 2019, https://doi.org/10.18061/ijsd.v10i0.6514), figure 14 was not included with the published HTML version of the article due to a production error. Figure 14 has been added to the HTML version of the article.